Penyesuaian Diri pada Mahasiswa Indigo di Universitas Islam Negeri Walisongo Semarang - Nuha, Salma Fathiyya; Sintya Dini Wilanda; Ana Nur Khasanah; Agni Setianingrum; Dewi Khurun Aini (Faculty of Ushuluddin and Humanities, 2024)
This study aims to understand how UIN Walisongo Semarang students who identify as indigo adjust to their situations. Using a qualitative phenomenological approach, the research involved three individuals living in Semarang. Interview questions were designed based on Schneiders’ self-adjustment characteristics. Data were collected through observations and interviews, with source triangulation to ensure data validity.Findings reveal that some indigo students adjust well, while others face difficulties. The first factor affecting self-adjustment is the strength of their indigo abilities; those with stronger abilities tend to have more trouble adjusting. The second factor is parenting.This study highlights the need for further research on the indigo phenomenon in Indonesia, where little scholarly attention has been given. Understanding these factors can help support indigo individuals in coping with their unique challenges.